Delay of Death Crime Execution With A 10 Year Probation Period From A Human Rights Perspective - Yohanes Gemilang Febrian; Tanudjaja (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
The research objective in this research report is to find out how human rights consider that someone who threatens public safety can be sentenced to death and to find out how judges consider in deciding cases of executing the death penalty with a probation period of 10 years.The research method used in this research is a normative juridical research method where the data sources come from laws, books, journals and the internet. The research approach used in this research is a qualitative approach. The results of the research in this writing are firstly thatThe existence of the death penalty in the legal system in Indonesia is reviewed from a human rights perspective, namely that it is contrary to human rights, especially the right to life. The two judges imposed the death penalty with a probationary period of 10 (ten) years taking into account: a. the defendant feels remorse and there is hope to improve himself; or b. the role of the defendant in the crime. The death penalty with a probationary period as intended must be included in the court decision. The grace period for the 10 (ten) year trial period begins 1 (one) day after the court decision obtains permanent legal force. Postponement of the execution of the death penalty which has been stipulated in writing in Article 100 of the National Criminal Code. In Article 100 paragraph (1) of the National Criminal Code, it is stated that the execution of the death penalty is determined by postponing the death penalty for 10 (ten) years which takes into account two conditions, namely, a feeling of regret and efforts to improve oneself and the role of the death penalty defendant in the crime. Furthermore, Article 100 paragraph (4) of the National Criminal Code states that if the convict has good behavior, then with a presidential decision based on the consideration of the Supreme Court, the death penalty can be changed to life imprisonment. Based on this background, the problem formulation in this research report is: How do human rights consider that someone who threatens public safety can be sentenced to death and how do judges consider when deciding on death penalty execution cases with a probationary period of 10 years.